2003
DOI: 10.1124/dmd.31.9.1081
|View full text |Cite
|
Sign up to set email alerts
|

SINGLE NUCLEOTIDE POLYMORPHISMS OF THE HUMANCYP2A13GENE: EVIDENCE FOR A NULL ALLELE

Abstract: This article is available online at http://dmd.aspetjournals.org ABSTRACT:Human CYP2A13 is believed to be important in the metabolic activation of tobacco-specific nitrosamines in the respiratory tract; therefore, genetic polymorphisms of the CYP2A13 gene may be associated with interindividual differences in the risks of tobaccorelated tumorigenesis. Our earlier studies identified a frequent single nucleotide polymorphism in CYP2A13 exon 5, Arg257Cys, which led to an approximate 50% decrease in metabolic activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
20
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 17 publications
0
20
0
Order By: Relevance
“…22) Another nonsense mutation polymorphism, C301T (CYP2A13*7 allele, Arg101Stop), which was detected in a Chinese population, is likely to be functionally important since it entails a severely truncated protein lacking enzymatic activity. 20) Zhang et al reported that this variant allele also exhibits a protective effect against procarcinogens in the respiratory tract. 20) This CYP2A13 C301T polymorphism has been associated with the risk of small cell lung cancer.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…22) Another nonsense mutation polymorphism, C301T (CYP2A13*7 allele, Arg101Stop), which was detected in a Chinese population, is likely to be functionally important since it entails a severely truncated protein lacking enzymatic activity. 20) Zhang et al reported that this variant allele also exhibits a protective effect against procarcinogens in the respiratory tract. 20) This CYP2A13 C301T polymorphism has been associated with the risk of small cell lung cancer.…”
Section: Introductionmentioning
confidence: 99%
“…18) Zhang et al 19,20) and Fujieda et al 21) have analyzed structural variations in the CYP2A13 gene. A C to T transition in exon 5 of the CYP2A13 (CYP2A13*7 allele, C3375T, Arg257Cys) has been shown to lead to a significant reduction in enzymatic activity (half the activity of the wild-type enzyme).…”
Section: Introductionmentioning
confidence: 99%
“…CYP2A13*3 and CYP2A13*7 were predicted to be null in function, and the other seven single nucleotide polymorphisms all resulted in missense variants (Table 1). The distribution frequencies of some CYP2A13 missense alleles have been investigated in Japanese, French Caucasian, and some other populations (Zhang et al, 2002(Zhang et al, , 2003Fujieda et al, 2003;Cauffiez et al, 2004Cauffiez et al, , 2005Cheng et al, 2004). However, to date, the distribution frequencies of all of the CYP2A13 missense alleles in Chinese Han population have not yet been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Nine nonsynonymous single-nucleotide polymorphisms have been identified for human CYP2A13, including an insertional frame-shift mutation (133_134T insertion, CYP2A13*3) and a substitution of a stop codon (R101X, CYP2A13*7) (Zhang et al, 2002(Zhang et al, , 2003Fujieda et al, 2003;Cauffiez et al, 2004Cauffiez et al, , 2005Cheng et al, 2004). CYP2A13*3 and CYP2A13*7 were predicted to be null in function, and the other seven single nucleotide polymorphisms all resulted in missense variants (Table 1).…”
Section: Introductionmentioning
confidence: 99%
“…Fewer than 70 SNPs of the gene have been reported in the NCBI dbSNP and Human CYP allele databases combined, and only a few of those have been functionally characterized. Since CYP2A13 was characterized, there have been few studies involving SNPs of the gene using PCR single-strand conformation polymorphism or direct sequencing for SNP analysis (21 ). Because of wide applications in pharmacogenomics and environmental cancer studies, there is a need for genotyping SNPs of CYP2C9 and CYP2A13.…”
mentioning
confidence: 99%